Pengaruh Debt Default, Kualitas Audit, dan Opini Audit Tahun Sebelumnya terhadap Opini Going Concern Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Zulvia Yeni Firnanda; Islahuddin Islahuddin; Syukriy Abdullah (Program Magister Akuntansi Unsyiah, 2015)
Responsibilities of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also assess the company's ability to maintain its survival. This is due to the demands of the shareholders to the auditor to provide early warning about the prospectsof a company as consideration before deciding on an investment decision. The objective of this research is to examine and analyze the influence of debt default, audit quality, and previous audit opinion toward going concern audit opinion at manufacturing companies listed at Indonesia Stock Exchange from 2010-2014. The research type used in this research is vericative research or hypothesis testing research.The sample consists of 105 manufacturing companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Bapepam consistently in the period 2010-2014. The data used in this research was secondary data and being selected by using purposive sampling method. The method of data analysis is using logistic regression analysis to measure going concern audit opinion. Results of this study demonstrate that the debt default and previous audit opinion have a positive relationship to going concern audit opinion. On the other side, audit quality do not have any influence towards going concern audit opinion. Simultaneous testing concluded that all the independent variables affect the dependent variable at 87,5 percent.KEYWORDS : debt default, audit quality, previous audit opinion, going concern audit opinion